Structural Interventions in the Basilica of the Recoleta Dominica in Santiago de Chile. a Historic and Critical Review; [Intervenciones Estructurales en la Basílica de la Recoleta Dominica en Santiago de Chile. Una Revisión Histórica y Crítica] - Barrientos-Monsalve, M (Universidad Diego Portales, 2024)
Unreinforced masonry (URM) historic churches are highly seismic vulnerable buildings due to its structural and material features. This condition partially explains the irreversible cultural heritage loss in Chile. After earthquakes, many URM churches have been strengthened with reinforced concrete (RC) elements as a seismic proof strategy. In this context, this paper aims to examine the Recoleta Dominica basilica, as a prominent building with architectural, historical, and constructive attributes with efficient seismic performance along years as well, as reported after the 1985 and 2010 megathrust earthquakes. Its seismic performance can be explained by the RC strengthening elements added after the 1927 earthquake, and later 1981-1982 and 2000 structural interventions, avoiding local collapses as serving its conservation. The paper concludes by highlighting the 1927 RC project impact, its early technique reflected on its structural design criteria and following the original building nature. Some other studies in this research line may contribute to a better understanding of the inherited scopes involved in any structural RC project, its impact on the architectural features, the seismic-resistant improvements, and its cultural preservation. © 2024 Universidad Diego Portales. All rights reserved.